The effect of residential factor on periodontal status among the primary school children in Ninevah Governorate/Iraq. (Mustansiria Dental Journal, 2004)
The purpose of the study was to determine the effect of residential factor on periodontal status (oral hygiene, gingival health and calculus assessment) among the primary school children in Ninevah.                ·An  oral health survey was conducted among 2640 primary school children aged 6 and 12 years old from 66 randomly selected schools in different geographical locations (urban, peri-urban and rural areas) ofNinevah Governorate.Examination of  periodontal status was performed using WHO periodontalprobe. The indices used to assess the periodontal status are (plaque index, gingival index and calculus index).The results showed th(lt (63.1%) of 6 year old and (29.5%) of 12 years old have a healthy gingiva. The prevalence of gingivitis was higher in rural than periurban and urban, with significant differences while no significant between boys and girls.The result indicated that the urban children have a lower significant mean gingival index score than peri-urban and rural areas.                               .According to the geographical locations, the children in urban and peri-urban areas  have less  mean  plaque  index  than  rural areas  with  significant differences between children of urban and rural areas of 6 years old children only. According to the sex difference, there were no statistically significant differences between the boys and girls.The study demonstrated that the mean of calculus index was almost similar in different areas for both 6 and 12 years old children, while according to the sex, the girls reported significantly lower mean that boys.